Effectiveness of Repetitive Transcranial Magnetic Stimulation Treatment on Depression - Birak, Ajuni (The Meducator, 2025)
Major depressive disorder (MDD) is a prevanlent mental health condition often treated with medication that may cause adverse effects, especially in younger individuals. Repetitive transcranial magnetic stimulation (rTMS) is a promising alternative for those who do not respond to traditional medications and methods of therapy. This noninvasive treatment targets brain regions associated with depression, such as the dorsolateral prefrontal cortex (DLPFC), using magnetic pulses to modulate neural activity. Current studies show that rTMS can improve response and remission rates with fewer side effects compared to standard treatments. Its safety profile, combined with its effectiveness for treatment-resistant cases, makes it a promising alternative to antidepressants. While current research on rTMS is limited by varying treatment durations and a lack of long-term data, rTMS presents as a valuable option for managing MDD.